Ibadan adolescent rebelliousness: attendant effects of self-esteem, gender, age, family type, peer influence and socioeconomic status (2016)
This study examined the psychosocial predictors of rebelliousness among school age adolescents in the Ibadan. Specifically, age, gender, family type, peer influence, socio economic status, and self-esteem formed the psychosocial predictors used in this study. Three research questions were raised and answered in the study; whereas the decisions on the questions were taken, at 0.05 level of significance. The research design used is descriptive survey of ex post-facto type. 421 in-school adolescents were randomly selected from five public secondary schools in Ibadan, Oyo State. The instruments used for this study were distributed to participants. Multiple regression statistics was employed to analyze the data collected from the participants. The results of the analysis indicated that all the independent variables jointly have 16% variance of rebelliousness of adolescents. Family type, socio-economic status, and self-esteem have significant contribution, whereas age and gender do not contribute significantly to rebelliousness of adolescents. In addition, only peer influence (r=.156) have significant relationship with adolescent rebelliousness at 0.05 level of significance. It was recommended that parents should be equipped with adequate parenting skills, whereas peer counselling should be organized for adolescents, as such will provide appropriate ways to respond to significant others that will devoid of rebelliousness.